Community-making in early Stuart theatres
1 online resource
Keywords: Twenty-two leading experts on early modern drama collaborate in this volume to explore three closely interconnected research questions. To what extent did playwrights represent dramatis personae in their entertainments as forming, or failing to form, communal groupings? How far were theatrical productions likely to weld, or separate, different communal groupings within their target audiences? And how might such bondings or oppositions among spectators have tallied with the community-making or -breaking on stage? Chapters in Part One respond to one or more of these questions by reassessing general period trends in censorship, theatre attendance, forms of patronage, playwrights' professional and linguistic networks, their use of music, and their handling of ethical controversies. In Part Two, responses arise from detailed re-examinations of particular plays by Shakespeare, Chapman, Jonson, Beaumont and Fletcher, Cary, Webster, Middleton, Massinger, Ford, and Shirley. Both Parts cover a full range of early-Stuart theatre settings, from the public and popular to the more private circumstances of hall playhouses, court masques, women's drama, country-house theatricals, and school plays. And one overall finding is that, although playwrights frequently staged or alluded to communal conflict, they seldom exacerbated such divisiveness within their audience. Rather, they tended toward more tactful modes of address (sometimes even acknowledging their own ideological uncertainties) so that, at least for the duration of a play, their audiences could be a community within which internal rifts were openly brought into dialogue.